2021
DOI: 10.1038/s41467-021-25061-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus coordinated Rh single-atom sites on nanodiamond as highly regioselective catalyst for hydroformylation of olefins

Abstract: Single-atom Rh catalysts present superior activity relative to homogeneous catalyst in olefins hydroformylation, yet with limited success in regioselectivity control. In the present work, we develop a phosphorus coordinated Rh1 single-atom catalyst with nanodiamond as support. Benefiting from this unique structure, the catalyst exhibits excellent activity and regioselectivity in hydroformylation of arylethylenes with wide substrate generality, i.e., with high conversion (>99%) and high regioselectivity (>… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 56 publications
4
72
1
Order By: Relevance
“…due to high chemical and thermal stability. Especially, Keggin-type heteropolyanions could lost one WO unit to offer vacant Keggin-type anions [XW 11 O 39 ] nÀ (X = P, n = 7; X = Si, n = 8) with significant coordinating ability through tuning pH value. Thus other transition metals can incorporate into the vacant POMs and afford a transition metal (e. g., Co, Ni, Fe, Mn, Ru, Pd, Pt, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…due to high chemical and thermal stability. Especially, Keggin-type heteropolyanions could lost one WO unit to offer vacant Keggin-type anions [XW 11 O 39 ] nÀ (X = P, n = 7; X = Si, n = 8) with significant coordinating ability through tuning pH value. Thus other transition metals can incorporate into the vacant POMs and afford a transition metal (e. g., Co, Ni, Fe, Mn, Ru, Pd, Pt, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…reported that single‐atom catalyst Rh 1 /ZnO can afford a comparable catalytic activity with that of RhCl(PPh 3 ) 3 in hydroformylation of styrene [8a] . Subsequently, single‐atom Rh catalysts including Rh 1 /CoO, [9] Rh 1 /CeO 2 [10] and Rh 1 /PNP‐ND [11] (nanodiamond‐supported phosphorus‐coordinated Rh 1 ) have also been reported for hydroformylation. These materials consist of the dispersed single metal atoms on a support and can enhance the utilization efficiency [12] of the precious Rh atoms remarkably (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%
“…Olefin hydroformylation is an important process in the industry to produce aldehydes and alcohols. , At present, homogeneous Rh complexes are widely used as catalysts for olefin hydroformylation with high activity and selectivity. , The difficulty of separating the catalysts from the reaction mixture remains a major technical challenge for the application of homogeneous catalysts. , Thus, significant efforts have been devoted to heterogeneous hydroformylation using Rh-based catalysts by anchoring Rh complexes, , Rh nanoparticles, or Rh single atoms on support materials. However, it is still challenging to improve the heterogeneous catalysts to be as efficient as their homogeneous counterparts for hydroformylation. , A better mechanistic understanding of olefin hydroformylation catalyzed by heterogeneous catalysts is crucial for the rational design of improved catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Atomically dispersed Rh atoms in Rh 1 /PNP‐ND (phosphorus coordinated Rh single atoms supported on nanodiamond) as confirmed by HRTEM, ac‐HAADF‐STEM and CO‐DRIFTs results show excellent catalytic performance for the hydroformylation of arylethylenes with wide substrate generality. [ 409 ] The Rh 1 /PNP‐ND catalyst reaches high conversion (> 99%) towards aldehyde and a high branched/linear aldehyde molar ratio of 13.3:1, which is commensurate with those of the homogeneous counterparts (Figure 21c). XAS and 31 P solid‐state NMR reveal that Rh single atoms are stabilized by the bidentate chelation with two P atoms, contributing to the good stability of six cycles without activity and selectivity decreasing under a controlled conversion of 77%.…”
Section: Bridging Heterogeneous and Homogeneous Catalysismentioning
confidence: 62%
“…Reproduced with permission. [ 409 ] Copyright 2021, Springer Nature. d) Hydroformylation of styrene to linear aldehydes over Rh 1 /CeO 2 catalyst, which is coupled with the low‐temperature water‐gas shift reaction (LWGS) without the use of ligands.…”
Section: Bridging Heterogeneous and Homogeneous Catalysismentioning
confidence: 99%